OCCURRENCE OF PAIN AND MUSCLE WEAKNESS IN POSTOPERATIVE PATIENTS WITH LOWER LIMB TRAUMA IN A HOSPITAL IN NORTH-CENTRAL GOIÂNIA (CIPEEX, 2025)
Postoperative pain is common and can delay recovery, impacting quality of life. Correct identification is crucial to avoid complications such as chronic pain and disability. Early mobilization helps preserve muscle strength (MS), but inadequate pain management can prolong rehabilitation. Thus, this study aimed to analyze the occurrence of pain and its association with muscle weakness in volunteers in the immediate postoperative period (PP) of lower limbs (LL) at a referral hospital in north-central Goiás. This is a cross-sectional study that investigated the relationship between pain intensity and muscle weakness, using the Visual Analog Scale (VAS) and the Medical Research Council (MRC) Muscle Strength Rating Scale, respectively, in postoperative patients with LLT in a hospital in north-central Goiás. A total of 92 volunteers were surveyed, with a mean age of 39.18 (+11.28) years, of whom 68.5% were male and 31.5% female. When stratified, the occurrence of pain was 59.8% mild, 32.6% moderate, and 7.6% severe. The analysis revealed that 46.9% of patients had significant weakness in the lower limbs. Although the average age was higher in the group with weakness, this difference was not significant (p = 0.142), indicating that factors other than age may influence muscle weakness in the postoperative period of lower limb trauma. The high prevalence of muscle weakness has important clinical implications, suggesting the need for future studies to explore other contributing factors.
Keywords: Postoperative pain; Muscle strength; Pain measurement; Rehabilitation